Fish fauna of Oussudu Lake, Pondicherry, South India - Chari, K B; Abbasi, S A (Indian Journal of Fisheries, 2011)
Oussudu Lake (commonly called â€œOusteriâ€ ) is a source of water and fishes to the people of Pondicherry region. The lake is now under serious threat of pollution and hence a study was conducted on the species composition and dynamics of the lake fishes. Recommendations pertaining to the management of water quality and fisheries are presented on the basis of the studies